Panorama das reservas particulares do patrimônio natural em Sergipe : uso do solo, representatividade ecológica e efetividade de gestão - Barreto, Valdelice Leite (2019)
Conservation units play a fundamental role in the preservation and conservation of natural resources. The set of these UCs make up the National System of Conservation Units - SNUC. The Private Reserve of Natural Heritage - RPPN, the subject of this research, is the only privately managed UC. The present study had as its general objective: to analyze environmental and sustainability characteristics involved in the management of RPPNs in the state of Sergipe, and as specific objectives: to know the alternative use of the soil in the properties where the RPPNs are inserted; estimate the ecological representativeness of RPPNs and evaluate the effectiveness of the management of RPPNs in the state of Sergipe. To characterize the alternative use of the soil, a field survey was carried out to collect points in Garmim navigation GPS in areas with vegetation and agrosilvipastoral activity, which, inserted in the images of Google Earht and RapidEye with the database of the Registration System Rural Environment (Sicar). For the analysis of the Ecological representativeness of the RPPNs, the calculation of the circularity index for each fragment of vegetation of the RPPNs was used and the methodology “Medición de la Efectividad de Gestão de Protected Areas - EMAP” was used to assess the effectiveness of management, pointing out the weaknesses and potentialities. The properties were characterized as for the alternative use of the soil: vegetal cover of the legal reserve areas, permanent preservation area and RPPN. Due to the low Circularity Index found, due to the isolation and the elongated shape of the forest fragments, it resulted in a low representativeness in the context of the RPPNs. The effectiveness of the management of the RPPNs, despite presenting a median standard of management quality, for the characteristics of protection and conservation, for the areas directly influenced by the existence of a management plan, the result was low, since only two of the RPPNs analyzed, have that document. As for the public authorities and the support provided by law, the result pointed out in the interviews was that there is a need for a closer relationship. It is deemed necessary an articulation between the owners and incentives from the public authorities for the elaboration of management plans, disclosure of benefits and implementation of incentive programs, such as the ICMS Ecológico so that there is a tendency to improve the management of existing RPPNs and encouraging the creation of new RPPNs as an important route in the conservation of natural resources in the state of Sergipe.